Glycaemic Control and Evidences of Ischaemic Heart Disease of Known Type 2 Diabetics Attending the Endocrinology Clinic at the Federal Medical Centre, Yenagoa, Nigeria - S. O. Ojeka; V. Z. Zabbey; R. B. Edward (Archives of Current Research International, 2023)
Introduction: Diabetes mellitus is a chronic disease with life-threatening complications with cardiovascular complications being the major cause of death among those with type 2 diabetes. Aim: The study was aimed at evaluating the glycemic status and evidences of Ischaemic heart disease, associated with type 2 diabetes mellitus among diabetic patients attending the endocrinology clinic in FMC Yenagoa during the study period. Materials and Methods: The study made use of 162 apparently healthy individuals and 300 diabetic patients. Interviewer-administered questionnaire and fasting blood sugar were the study tools. The data obtained were analyzed using descriptive statistics and paired sample T-test. Results and Discussion: The results revealed that the body mass Index, Blood Pressure and Fasting Blood Sugar of the diabetics were significantly higher than those of the non-diabetics. Again, 41.7% of the experimental subjects had a normal glycemic control, 49.7% had a fair glycemic control while 8.7% of them had a poor glycemic control. The symptoms of Ischaemic heart disease associated with type 2 diabetes in the experimental subjects were chest pain, chest discomfort, pain in the leg, ischaemic gangrene and loss of strength. Again, age, gender, Body mass index, smoking and Fasting blood sugar were other risk factors found to be associated with ischaemic heart disease. Conclusion and Recommendation: Implementing lifestyle changes such as regular exercise, a healthy diet, and smoking cessation to reduce the risk of cardiovascular abnormalities in diabetics is recommended. A close and regular monitoring of the Fasting blood sugar, Blood Pressure and cardiac abnormalities is also recommended for diabetic patients.